Investigation of Honeycomb Sandwich Panel Structure using Aluminum Alloy (AL6XN) Material under Blast Loading - Dany Taufiq Alim Ansori; Aditya Rio Prabowo; Teguh Muttaqie; Nurul Muhayat; Fajar Budi Laksono; D. D. Dwi Pria Tjahjana; Ari Prasetyo; Yemi Kuswardi (Salehan Institute of Higher Education, 2022)
In this study, we focused on the large inelastic behavior of a sandwich panel made of two solid plates as a stiffener and a honeycomb core shell subjected to blast load. The loading scheme was carried out using an explosive charge bullet mounted at a standoff distance of 100 mm with three mass variations of trinitrotoluene: 1, 2, and 3 kg TNT. The numerical simulations performed using ABAQUS/CAE were validated with the experimental results of a previous study. The geometrical effects of the sandwich panel on intact and damaged models were also numerically investigated. The panel was designed using a square and hexagonal honeycomb core. The effect of honeycomb core height was also observed by modeling the core using three height variations: 31, 51, and 71 mm. The results showed that the hexagonal core was more resistant to blast loads than the square design. The core height parameter determines the energy absorption based on these results. The structural strength is also affected by the damage. The findings of this study can be used to improve structural designs that utilize sandwich panels to withstand blast loads. Doi: 10.28991/CEJ-2022-08-05-014 Full Text: PDF